ANALISIS EVALUASI PEMBELAJARAN PENDIDIKAN PANCASILA TERHADAP PENCAPAIAN KOMPETENSI PESERTA DIDIK SEKOLAH DASAR - Putri Mas Intan Silalahi; Dian Armanto; Anita Yus (STKIP Subang, 2026)
This study aims to examine the implementation of Pancasila Education learning evaluation in relation to the achievement of elementary school students' competencies, specifically regarding norms in grade V of SDN 060933 Medan Johor. This study used a descriptive qualitative approach involving homeroom teachers and students as research subjects. Data were collected through observation, interviews, and documentation, then analyzed inductively. The results indicate that Pancasila Education learning evaluation activities have covered three aspects of assessment: cognitive, affective, and psychomotor. However, implementation in the field remains uneven. Assessment still predominantly focuses on the cognitive aspect, while attitudes and skills have not been systematically measured. Factors influencing student competency achievement include learning strategies, media use, and active student participation during the learning process. Therefore, the development of a more authentic and comprehensive evaluation system is needed so that Pancasila Education learning outcomes can reflect the development of students' character and understanding of citizenship comprehensively.